Breast cancer survival and the health system in Brazil: an analysis of public and private healthcare - Ferreira, Adriana de Souza Sérgio; Cintra, Jane Rocha Duarte; Fayer, Vívian Assis; Nogueira, Mário Círio; Júnior, Cassimiro Baesso; Bustamante-Teixeira, Maria Teresa; Chaoubah, Alfredo; Cintra, Arthur Duarte; Simão, Caroline Montes; Guerra, Maximiliano Ribeiro (Frontiers in Oncology, 2023)
Background: Breast cancer incidence is increasing worldwide; however, survival outcomes vary, being lower in developing countries. Methods: We analyzed five- and ten-year survival for breast cancer according to the type of health care insurance (public vs. private), in a referral center for cancer care in the Brazilian Southeast region. A hospital-based cohort study was carried out with 517 women diagnosed with invasive breast cancer between 2003 and 2005. The Kaplan-Meier method was used to estimate the probability of survival and Cox's proportional hazards regression model to assess prognostic factors. Results: Five and ten-year breast cancer survival were, respectively: private health care service: 80.6% (CI95% 75.0-85.0) and 71.5% (CI95% 65.4-77.1); public health care service: 68.5% (CI95% 62.5-73.8) and 58.5% (CI95% 52.1-64.4). The main factors associated with the worst prognosis were the presence of lymph node involvement in both health care services and tumor size >2 cm only in public health service. The use of hormone therapy (private) and radiotherapy (public) were associated with the best survival. Conclusions: The survival discrepancies found between health services can be explained mainly by the difference in the stage of the disease at the time of diagnosis, indicating inequalities in access to early detection of breast cancer.